Menuju Indonesia Bebas Karies Tahun 2030 Melalui Upaya Promotif dan Preventif Kesehatan Gigi Anak Usia Sekolah Dasar di SDIT Cahaya Hati Bukittinggi - Nova Herawati; Lisnayetty; Syukra Alhamda (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2023)
Dental caries is a dental health problem that has a major impact on individuals and society in terms of pain and suffering, functional impairment and reduced quality of life. The aim of this activity is to increase children's knowledge and self-care behavior in the field of dental health, improve dental and oral hygiene, and prevent dental caries in children in order to move towards a Caries-Free Indonesia 2030. The implementation method includes promotional efforts, namely counseling and demonstrations, efforts Prevention includes plaque control, joint toothbrushing and early detection of dental caries. The results of the activities increased the knowledge of SDIT Cahaya Hati students about dental health through dental health education activities. Increased tooth brushing behavior and dental and oral hygiene status of students through joint tooth brushing activities. The prevalence of caries among students at Cahaya Hati Elementary School, Bukittinggi City is 80.2% with an average DMFT of 4.1, meaning that each child has 4 teeth with caries experience which is dominated by the Decayed (D) component, namely 2.7, meaning that each student needs 2 teeth filling treatment. 3 teeth. 79.3% of students have tooth surfaces free from tartar. Conclusion: Increased knowledge of SDIT Cahaya Hati students about dental health and the impact of smoking on dental health.